Revisiting the taxonomy of Colletotrichum using multi-locus gene phylogeny - CHOWDAPPA, P. (Indian Phytopathology, 2017)
Dear members of the Indian Phytopathological Society (IPS) and delegates of the National Symposium. I am privileged to represent our society as the President and to follow and strengthen the philosophy and scientific contribution of the previous leading scientists, who have served as Presidents. This is a formidable task, yet I derive strength and inspiration from our executive committee. Please join me in welcoming our IPS members and delegates to the IPS 69th Annual Meeting and National Symposium on â€œDiagnosis and Management of Plant Diseases: Integrated Approaches and Recent Trendsâ€ held at ICAR Research Complex for NEH Region, Umiam, Meghalaya during January 09-11, 2017. Moreover, I would like to extend many thanks for the involvement and contribution of the executive committees at Zonal and national levels, who have been essential in keeping our society running actively and soundly. The society will continue to providing support and, in some cases, guidance, for the organization and development of courses, seminars, workshops and zonal meetings in different parts of the India for reducing crop losses caused by plant pathogens.